CODE-SWITCHING IN VIEWER COMMENTS ON AN INDONESIAN EDUCATIONAL YOUTUBE CHANNEL - Caku Caku; Gabriela Apriani Koli; Axel Emmanuel Herman Jr. Kolatlena; Ouda Teda Ena (STKIP Persada Khatulistiwa Sintang, 2026)
This study investigated code-switching patterns in viewer comments on the Indonesian educational YouTube channel